Emergence of Rohingya Refugee: Present Situation and Future Impact on Local Peoples of Cox’s Bazar in Bangladesh - Anwar Hossain Choudhury (Randwick International of Social Science Journal, 2020)
Rohingya crisis is not a newly emerged problem in Bangladesh. Almost two and half years ago, it has been emerged as a great problem in Bangladesh, because of the quantity of Rohingya refugees. The main objective of the study is to understand the present and future situation of Rohingya refugee at cox’s bazaar in Bangladesh and its impact on local people of cox’s bazar. That will include social strains, political impact, security challenges. Economic effects, environmental destruction etc. The study is based on primary data will be collected from Rohingya refugee from Teknaf Upazila of Cox’s Bazar in Bangladesh. Cox’s bazar to find out the present situation and future impact for emerging Rohingya refugee on local people of cox’s bazar. Which could help to identify the problems of Rohingya refugee for Bangladesh context.